Alcohol consumption and cerebrospinal fluid biomarkers for preclinical alzheimer’s disease in a population-based sample of 70-year-olds - Silke Kern; Tobias Skillbäck; Henrik Zetterberg; Anna Dittrich; Felicia Ahlner; Anna Zettergren; Margda Waern; Nazib M Seidu; Ulf Andreasson; Kaj Blennow; Ingmar Skoog (Alzheimer’s Research & Therapy)
Abstract Background It is largely unknown how alcohol use affects the risk of Alzheimer`s disease (AD). Therefore, studies on the influence of alcohol use on cerebrospinal fluid (CSF) biomarkers for the earliest preclinical phase of AD are needed. Methods This was a cross-sectional cohort study. The sample (n = 301) was derived from the 2014–2016 examinations of the Gothenburg H70 Birth Cohort Studies. The study cohort consisted of 301 70-year-old women and men, where of 246 cognitively unimpaired and 55 with mild cognitive deficits. Information on alcohol consumption (g/week and type of alcohol) was collected and CSF amyloid-β1−42 (Aβ42), total-tau (T-tau), tau phosphorylated at threonine 181 (P-tau181), neurofilament light protein (NfL) and neurogranin (Ng) were measured. We tested the association between the CSF biomarkers and alcohol consumption types using correlation and linear regression, adjusting for possible confounders when necessary according to the performed sensitivity analysis. Results There were no correlations between weekly alcohol consumption and any of the CSF markers studied in the total sample of cognitively unimpaired participants (n = 246). After adjustments for multiplicity with FDR, there was an association between white wine and Ng in women with CDR = 0 (β:0.254, CI: ( 0.069: 0.439), p = 0.0076, FDR = 0.0455). Interaction analysis between female sex and red wine intake was a significant predictor of high Ng levels (β:0.410, CI: ( 0.099: 0.721), p = 0.0100, FDR = 0.0500). There were no correlations between consumption of specific types of alcohol (spirits, white wine, red wine, fortified wine, and beer) and any of the biomarkers studied in the total sample of cognitively unimpaired participants. Conclusions Our findings indicate that higher alcohol use in older cognitively unimpaired women correlates with a biomarker of synaptic dysfunction in AD, which is an important observation in a time when alcohol use is increasing among women.